Analysis of Nitrogen and Potassium in Liquid Organic Fertilizer from Rice Washing and Mature Coconut Water - Pinkan K. Bolang; Vanny M. A. Tiwow; Paulus H. Abram; Yuli Nurmayanti (Universitas Tadulako, 2025)
Mature coconut and rice washing water contain nitrogen and potassium, which are helpful for plants. This study aims to determine the levels of nitrogen and potassium in liquid organic fertilizer from a mixture of mature coconut water and rice washing water. Nitrogen content was analyzed using the Kjeldahl method. Potassium levels were analyzed using a flame photometer. The results indicated that the best nitrogen and potassium levels were obtained in liquid organic fertilizer with a mixture ratio 50:50, namely N 1.26% and K 1.27%. The highest nitrogen content was obtained in liquid organic fertilizer (LOF) with a mixture ratio of 25:75, 1.40%, and the highest potassium content was obtained in liquid organic fertilizer with a mixture ratio of 50:50, 1.27%. When mixed, the increase in nitrogen and potassium levels was caused by the bacteria in the liquid organic fertilizer, which breaks down protein during digestion.